Там, где русская слава прошла - Маковеев Василий Филимонович (ВМ, 1989)
Экземпляры: КХ (20101207) / Инвентарный номер: 943962 / Цена: 0.90 / Сис.шифр: 63.3(2)722 / Авт.знак: М 16 / ГРНТИ: 03 / ББК: 63.3(2)622-35